Chapter Verso le neuroscienze del processo progettuale - Arbib, Michael (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Introduces some key notions of cognitive (neuro)science including mirror neurons and perceptual and motor schemas. Much important processing may be subconscious. Af-fordances link multi-modal perception and action. Three linkages of architecture and neuroscience are noted: neuroscience of experience; neuroscience of design; and neuro-morphic architecture, "brains" for buildings. Examples are offered from Zumthor's Therme at Vals (linking memory and imagination) and a case study of group creativity in choreography (illustrating four-dimensional planning).